Numerical Data Clustering Algorithms in Mining Real Estate Listings - Krzysztof Pancerz; Olga Mich (Barometr Regionalny)
In the paper, we propose a method for mining real-estate listings using clustering algorithms intended for numerical data. The presented approach is based on information systems over ontological graphs. Such information systems have been proposed to deal with data in the form of concepts linked by different semantic relations. A special attention is focused on preprocessing steps transforming advertisements in the textual form into information systems defined over ontological graphs, as well as on encoding attribute values for clustering algorithms.